2020
DOI: 10.1186/s42269-020-00314-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro culture conditions affecting propagation of mulberry plant

Abstract: Background: Mulberry Morus spp. L. Family Moraceae is a perennial tree crop cultivated worldwide for foliage, fruit, fuel wood, and medicine, as well as for several other sericulture and industrial purposes. Mulberry trees are grown in more than 50 countries covering temperate, subtropical, and tropical zones as a plantation crop. Methodology: In this study, different stages of in vitro propagation mulberry plant were investigated. In the sterilization stage, different concentrations 0.1, 0.2, and 0.3 (%) of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…A two-step sterilization process with ethanol was found to be effective in a previous study [25,27,29], which is in harmony with our findings. In our study, EtOH with NaClO also provided the best results for all observed parameters.…”
Section: Sterilization Stagesupporting
confidence: 93%
See 2 more Smart Citations
“…A two-step sterilization process with ethanol was found to be effective in a previous study [25,27,29], which is in harmony with our findings. In our study, EtOH with NaClO also provided the best results for all observed parameters.…”
Section: Sterilization Stagesupporting
confidence: 93%
“…On the contrary, another study conducted with Arbutus unedo showed that increasing doses of BAP clearly increased the number of shoots [35], as in our studies. They showed that the multiplication rate increases with the amount of BAP, whereas the rate of elongation was found to decrease in another study [27]. However, some other researchers found that increasing doses of BAP caused decreasing proliferation rates with production of only a few small microshoots [32].…”
Section: Proliferation Stagementioning
confidence: 93%
See 1 more Smart Citation
“…Vegetative and sexual reproduction are both present in the mulberry (Morus sp.). Depending on their soil type and environmental conditions, several countries employ a variety of propagation techniques (Taha et al, 2020). Mulberry plants are propagated sexually by using the seeds of mature fruit to make new plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth of axillary shoots can be promoted by this reduction in apical dominance (Mangena, 2020). Furthermore, the research of Taha et al (2020) found that the addition of 1 mg/l NAA to the MS medium resulted in improved development and growth of the mulberry root system, leading to successful acclimatization.…”
Section: Introductionmentioning
confidence: 99%